Thermal oxidation activation of hydrochar for tetracycline adsorption: the role of oxygen concentration and temperature. (June 2020) - Huang, Hua; Niu, Zhirui; Shi, Ruru; Tang, Jingchun; Lv, Lei; Wang, Jian; Fan, Yimo
Graphical abstract: Highlights: Hydrochar was thermal activated above 500 °C with O2 concentration as low as 0.5%. Hydrochar activated at 500 °C was with highest surface and tetracycline adsorption. Tetracycline adsorption was enhanced by pore filling and π-π interactions. Activation at 700 °C transformed micropores into mesopores but decreased surface. Abstract: Poplar hydrochar (RHC) was activated by thermal oxidation (TA-O) in air at 300 °C (O300) and in air + N2 (0.5% O2 ) at 500 and 700 °C (O500 and O700), respectively, and in N2 at 300–700 °C (N300–N700) as control. Samples characterized by various methods were used to analyze their effect on tetracycline adsorption. The results showed that TA-O greatly increased adsorption capacity qe, 100 (mg·g −1, C0 = 100 mg·L −1 ) from 6.29 for RHC to 33.32, 96.23 and 60.90 for O300, O500 and O700, respectively. The O300 increased carboxyl and aromaticity whereas little influenced on porosity. The O500, with the highest SBET and Smicro, enhanced adsorption probably by micropore filling and π-π interactions. The O700 fused micropore into mesopore but decreased the SBET, Smicro and qe, 100 . Thus, thermal oxidation at 500 °C and 0.5% O2 is recommended for hydrochar activation to absorb tetracycline.